Productivity Analysis Using the Multi Factor Productivity Measurement Model (MFPMM) as an Effort to Increase Competitiveness (Case Study: WL Alumunium Yogyakarta) - Grita Supriyanto Dewi; Khairun Nadiyah (Journal of Industrial Engineering and Halal Industries, 2022)
It is known that the national economy is dominated by Cooperatives and Small & Medium Enterprises (SMEs), this proves that Cooperatives and SMEs have competitiveness and potential that must be maintained. WL Aluminum is an SME located in the Yogyakarta area which is engaged in the metal casting industry with products that include frying pans, citel, pans and other kitchen utensils. In order for a business to survive and continue to grow, it must be able to compete by preparing various strategies so that the products it produces will always exist in the market. One form of strategy that can be used is by measuring the company's productivity. This is used to determine the extent to which the effectiveness of the product produced and the efficiency of the use of available resources. Several variables that affect productivity include raw materials, energy and labor. The purpose of this research is to find out what the productivity index (PI) is for WL Aluminum using the MFPMM, and to find out whether there is an influence between the profitability received by WL Aluminum and productivity and price changes using the Multiple Linear Regression method. The results of productivity calculations using the MFPMM show that PI was in a row October-November 2015, November-December 2015; December-January 2016; January-February 2016; February-March 2016; March-April 2016; April-May 2016 of 1.0064; 1.2370; 0.8545; 0.9016; 0.9607; 1,1,068; 0.7348. The results of the mathematical equation using Multiple Linear regression are profitability (Y): -0.952+ 1.001 productivity (x1) + 0.951 price recovery (x2). Testing with the F test shows that the calculated F value is 1401891.948 with a significance value of 0.000 <0.05. This proves that profitability is influenced by productivity and price changes.